High yield synthesis of high-silica chabazite by combining the role of zeolite precursors and tetraethylammonium: SCR of NOx1. Issue 49 (21st June 2015) - Martín, Nuria; Moliner, Manuel; Corma, Avelino
<x xml:space="preserve">Abstract</x> The synthesis of chabazite with high solid yields is achieved by the rational combination of directing effects of a source of Si and Al coming from USY zeolites and the inexpensive tetraethylammonium.